2018
DOI: 10.1159/000489592
|View full text |Cite|
|
Sign up to set email alerts
|

Association of MiRNA-146a, MiRNA-499, IRAK1 and PADI4 Polymorphisms with Rheumatoid Arthritis in Egyptian Population

Abstract: Background/Aims: Rheumatoid arthritis (RA) is a systemic autoimmune disease affecting up to 1% of the population worldwide. The aim of the present study was to investigate whether miRNA-146a rs2910164, miRNA-499 rs3746444, IRAK1 rs3027898 and PADI4 rs1748033 polymorphisms are associated with susceptibility to RA in Egyptians and whether they influence disease severity and activity. Methods: The study was performed on 104 unrelated RA patients and 112 healthy subjects. RA patients were further subdivided into a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…The thermocycling conditions were as follows: 45 PCR cycles at 92˚C for 15 sec; denaturation at 95˚C for 10 min; and annealing and extension at 60˚C for 90 sec. Real-time PCR was performed using a Rotor-gene Q Real-Time PCR system (Qiagen, Inc.) (27).…”
Section: Methodsmentioning
confidence: 99%
“…The thermocycling conditions were as follows: 45 PCR cycles at 92˚C for 15 sec; denaturation at 95˚C for 10 min; and annealing and extension at 60˚C for 90 sec. Real-time PCR was performed using a Rotor-gene Q Real-Time PCR system (Qiagen, Inc.) (27).…”
Section: Methodsmentioning
confidence: 99%
“…Rheumatoid arthritis (RA) represents a type of autoimmune joint inflammatory disorder and has been reported to affect approximately 6% of people over 65 years old, while showing predominance in women more so than men [1]. The chief characteristics of RA include hyperplasia synovitis and inflammatory immune cell infiltration [2].…”
Section: Introductionmentioning
confidence: 99%
“…They play an important role in regulating transcription and translation [36]. Some studies indicated that they also participate in cell proliferation, differentiation, and apoptosis [7, 8]. And, miRNAs can cause the degradation or translation repression of their target miRNA by binding to the 3′-untranslated region of specific mRNAs (messenger RNAs) [912].…”
Section: Introductionmentioning
confidence: 99%